Akidah Imāmah Shī`ah dalam Konteks Doktrin Wilāyah al-Faqīh Khomeini: Suatu Analisis Simbiotik - Zainal Abidin, Azmil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
The listing of twelve imāms implies a freeze imposed on the presence of weaknesses of the Shī`ah Imāmiyyah world in addressing the political crisis. Islamic law cannot be fully implemented without the arrival of Imam Mahdī or ‘Ṣāḥib al-Zamān’. As a result, the world of the Shī`ah is shrouded in a kind of passive attitude in the face of challenges against the tyranny of the ruler until the reconceived of Wilāyah al-Faqīh doctrine which was studied by Khomeini inspired by the Iranian Islamic Revolution in 1979. The Shī`ah community adopted Khomeini as a successful mujaddid figure who had succeeded in effecting a paradigm shift and reliving the classic imāmah faith. Furthermore, this doctrine had gained the sympathy of the Sunni community who had only accepted it as a moral victory upon the political landscape dominated by Western secular powers. Symbiotically, the Wilāyah al-Faqīh doctrine has to be conceived for the sake of the relevance of the imāmah faith in addressing the critical situation of the Shī`ah world, while sinless imam faith ‘had’ to be changed to the fiqah selection of “unseen deputy imam” based on consultation. The Wilāyah al-Faqīh doctrine is a co-ordination mechanism of the Shī`ah in overcoming the impasse in the interpretation of Islamic political history the doctrine of the badā’, taqiyyah, `iṣmah and raj`ah. To look at it positively, this doctrine has triggered an awareness to enhance the position of Islamic scholars to guide Muslim leadership. Ironically, this doctrine clearly shows the paradoxical side besides their criticism against the political theory of the Sunni based on shura, at once proving vulnerability and confusion of the Imāmah faith indoctrinated since a long time ago.